Legal Consequences of the Auction of the Auction Object Related to the Beneficial Owner of the Auction Object Over the Buyer - Salsabila, Amira Choirunnisa; Anshari, Tunggul; Widhiawati, Dyah (IJBLE Scientific Publications Community Inc., 2025)
A competitive auction consists of a public sale managed by a second manager, where sellers and buyers exchange assets as specified in mutual documents. According to the provisions of Article 38(c) of the Financial Regulation No. 4662; these officials cannot purchase goods directly or indirectly in their presence, in accordance with the Secondary Officials Law No. 189/PMK.06/2017. However, the fact that the legislation does not specify specific conditions regarding the concept of